Review of the Article : “Activities and Programs That Improve Children’s Executive Functions” - Cortés Saavedra, Daniela; Marques, Daniela (Pensando Psicología, 2016)
This review elaborates on an argument that describes the relevance of studying executive functions in the context of assessment and intervention. The main topics discussed in the article, such as conceptualization of executive function, general principles of intervention and effectiveness of some training programs, are described. It concludes by emphasizing the need to explore different intervention methods to choose the one that best suits the individuality of each subject. Similarly, the interest of the vast majority of researchers in studying training methods aimed at schoolchildren, putting aside those who are not linked to a formal education process, is criticized.